The use of injectable calcium hydroxylapatite in the surgically pretreated larynx with glottal insufficiency. (31st August 2016) - Caffier, Philipp P.; I. Nasr, Ahmed; Weikert, Sebastian; Rummich, Julius; Gross, Manfred; Nawka, Tadeus
Abstract : Objectives/Hypothesis: To evaluate the efficacy of vocal fold (VF) augmentation with calcium hydroxylapatite (CaHA) microspheres in the surgically pretreated larynx with glottal insufficiency. Study Design: Prospective clinical pilot study. Methods: After several prior reconstructive attempts (following tumor resection, VF paralysis, in sulcus vocalis, and VF scarring), CaHA was injected under general anaesthesia using a transoral microlaryngoscopic approach in 10 patients with residual glottal insufficiency ≤1.5 mm. The postinterventional result was assessed after 1 day, and 1 and 3 months. Evaluation of augmentation comprised intraoperative video/photo documentation, pre‐/postoperative videolaryngostroboscopy, as well as established subjective and objective voice function diagnostics (Grade, Roughness, Breathiness [GRB] Scale; Voice Handicap Index; voice range profile; and acoustic‐aerodynamic analysis). Results: In the pretreated VF with no or minimal lamina propria remaining, the exact placement of CaHA was not possible due to unpredictable propagation into the scarred tissue. The results showed an insufficient postoperative augmentation. Accordingly, the voice function did not improve. However, a significant increase of the vocal range from 6.2 ± 3.2 to 8.7 ± 3.9 semitones was observed in the speaking voice profile ( P =.02). All other acoustic and aerodynamic parameters remained on the whole unchanged; the slight differences between pre‐ and postoperative findings were not significant. Conclusions: The application of CaHA in the surgically pretreated scarred larynx is not reliable to achieve a sufficient glottal closure and a satisfactory improvement of voice. Though CaHA is a welcome addition to our armamentarium against glottal insufficiency, the suitability for augmentation of scar tissue in the larynx must be considered carefully in each individual case. Level of Evidence: 4 Laryngoscope, 127:1125–1130, 2017